Beneficial properties of lactic acid bacteria isolated from a Rana catesbeiana hatchery - Pasteris, Sergio Enrique (2009)
This work addresses the selection of potentially probiotic lactic acid bacteria (LAB) to be used in raniculture. Thus, strains belonging to the genera Pediococcus pentosaceus, Leuconostoc mesenteroides, Lactococcus lactis and Enterococcus faecium isolated from a Rana catesbeiana hatchery were evaluated for their inhibitory properties against RLS‐associated pathogens (Proteus vulgaris, Pseudomonas aeruginosa, Staphylococcus epidermidis) and food‐borne bacteria. Cell‐free supernatants of LAB strains inhibited the growth of at least one of the pathogens by organic acids, but L. lactis CRL 1584 also produced a bacteriocin‐like metabolite. The ability of LAB strains to produce H2O2 in MRS+TMB medium was also studied. Seventy‐eight to ninety six per cent of the strains showed some level of H2O2 production. Moreover, different organic solvents were used to determine the hydrophobicity and Lewis acid/base characteristic of LAB strain surfaces. Most of the strains presented hydrophilic properties, but no acidic or basic surface characters. However, some strains isolated from the skin showed a high degree of hydrophobicity and basic components in the cell surface due to their adhesion to chloroform. These properties were not observed in LAB from balanced feed and freshwater. Taking into account general guidelines and the beneficial properties studied, five strains were selected as potential candidates to be included in a probiotic for raniculture.